PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF DEVELOPING LOGICAL REASONING AND CRITICAL THINKING IN STUDENTS - Kamola Daniyarova; Samarat Mambetazhieva; Kitibayeva Alfiya Kanibekovna (International Journal of Literature and Language Studies, 2026)
Abstract. Logical reasoning and critical thinking are the issues which are studied by the scholars around the world. According to psychologists, preschool and primary school age is a period of active psychological development. An important feature of this stage of life is that significant changes occur in all areas of a child's development. Mental and physiological functions improve, complex personality formations appear. Childhood development is the process of physical, social, and cognitive growth that begins at birth and ends at adulthood. Natural or biological factors, including variables such as genetics and nutrition, as well as social elements such as upbringing and other environmental factors, are important factors in a child's development. This article analyzes the pedagogical and psychological features of developing logical reasoning and critical thinking in students of elementary level students.